Urogenital Myiasis in a 5 Years Old Boy: A Case Report - Nader Shakib Azad; Mohsen Kalantari; Masoumeh Amin; Afshin Barazesh (Iranian Journal of Parasitology)
Myiasis infection is caused by the invasion of flies' eggs and larvae into different tissues of the host's body. The rarest form is urogenital myiasis, which can occur even in men with a much lower probability than women, especially in tropical and subtropical regions. The case of this study is a 5-year-old boy from suburbs of Bushehr City, southern Iran who referred to the Pediatrics Department of Persian Gulf Hospital in Bushehr due to constant fever and significant weight loss. In urine evaluation, the presence of Chrysomya bezziana larvae was confirmed. The larvae of several species of myiasis-producing flies can attack the urinary-genital system of people and cause urogenital symptoms. Therefore, it is necessary to diagnose and accurately identify the species of larvae that cause myiasis in order to properly treat affected patients.